2016
DOI: 10.3233/nre-161331
|View full text |Cite
|
Sign up to set email alerts
|

Predictive validity of the Spinal Cord Injury Pressure Ulcer Scale (SCIPUS) in acute care and inpatient rehabilitation in individuals with traumatic spinal cord injury

Abstract: The SCIPUS could predict PrU occurring within 2-3 days following administration during acute, but unable to predict over a longer term within acute or inpatient rehabilitation. Improved PrU risk assessment following SCI may be possible with modification to the SCIPUS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Effectively repositioning patients at every 2 hours would require more manpower in a public health system stricken by chronic budget issues. Use of a prediction score such as the SCI Pressure Ulcer Scale (SCIPUS) could be beneficial for identifying patients with higher risk of PUs 17,18 and could result in better resource allocation. Pneumonia rates in our population were similar to other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Effectively repositioning patients at every 2 hours would require more manpower in a public health system stricken by chronic budget issues. Use of a prediction score such as the SCI Pressure Ulcer Scale (SCIPUS) could be beneficial for identifying patients with higher risk of PUs 17,18 and could result in better resource allocation. Pneumonia rates in our population were similar to other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Krishnan et al [58] studied the scale's use in emergencycare and rehabilitation-care units. The whole study was divided into 2-3-day and 5-7-day segments in emergency care and 5-7-day segments and 14-21-day segments in rehabilitation care.…”
Section: Pressure Ulcer Risk Assessment With the Spinal Cord Injury Pmentioning
confidence: 99%
“…The subcategories of concomitant diseases (where pulmonary and heart diseases or autonomic dysreflexia are included) and blood tests measuring albumin, creatine, and glucose are particularly contributive for physically handicapped patients. The scale is recommended in acute care, particularly for 2-or 3-day registration of risk factors in patients with spinal cord damage and other traumas leading to a physical handicap [18]. The scale was compared with the Norton, Braden, Hosnell, and Waterlow scales, and the results showed that SCIPUS had a higher level of data complexity.…”
Section: Introductionmentioning
confidence: 99%
“…The Braden Risk Assessment Scale is hampered by ceiling effects in the SCI population . Among the other available instruments, only the Spinal Cord Injury Pressure Ulcer Scale (SCIPUS) has shown promise, with a high rate of inter‐rater reliability . However, it is limited by utility issues, a lack of psychometric testing, and effectiveness that is dependent upon care setting.…”
Section: Background and Introductionmentioning
confidence: 99%